2019
DOI: 10.5812/aapm.67835
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effect of Nature-Based Sounds Intervention and Headphones Intervention on Pain Severity After Cesarean Section: A Prospective Double-Blind Randomized Trial

Abstract: Background Non‐pharmacological treatment methods are being increasingly investigated for pain prevention and relief either alone or in combination with pharmacological treatment. Methods The present randomized placebo-controlled trial was conducted on 57 mothers undergoing elective cesarean section over 10 months from April 2015 to February 2016. The participants were randomly assigned to three groups: control, headphone, and nature-based sounds (N-BS). The investigator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
(23 reference statements)
1
14
0
2
Order By: Relevance
“…A comparison of a fixed time‐interval with on‐demand oral analgesia concluded that the former was associated with better pain scores [129]. One study evaluated the use of relaxation sounds intra‐ or postoperatively and showed improved pain scores [130]. One study evaluated the use of early skin‐to‐skin contact between mother and baby and noted no differences in postoperative pain scores [131].…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of a fixed time‐interval with on‐demand oral analgesia concluded that the former was associated with better pain scores [129]. One study evaluated the use of relaxation sounds intra‐ or postoperatively and showed improved pain scores [130]. One study evaluated the use of early skin‐to‐skin contact between mother and baby and noted no differences in postoperative pain scores [131].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a systematic review noted multiple analgesics for their ability to relieve acute postoperative pain by half over a 4-6-hour period [44]. In our study, to potentialize VR effects, we chose various auditory (eg, alpha/theta binaural beats, nature-based sounds) and visual (eg, bilateral alternative stimulations) therapeutic procedures known to relieve pain in different conditions (eg, premenstrual pain, medical imaging procedures, experimental pain, or caesarean section [25][26][27]). Lucine aimed to combine these stimuli into the DTx treatment Endocare to act on different components of pain.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…On these bases, a new digital therapeutic approach, Endocare, was created by combining various therapeutic procedures based on several modalities in a VR environment, individually known to reduce pain [25][26][27]. Endocare therapeutic procedures comprise auditory (eg, alpha/theta binaural beats, nature-based sounds) and visual (eg, bilateral alternative stimulations) components associated with a 3D VR environment.…”
Section: Introductionmentioning
confidence: 99%
“…The biophilia hypothesis -where humans have an innate and natural affiliation with nature (Wilson, 1986) -has traditionally been central to the proposed link between greenspace exposure and health outcomes, and relates to exposure to the sights and sounds of nature. Listening to pleasant nature sounds during elective Caesarean section has been shown to reduce post-operative pain severity (Farzaneh et al, 2019), and also resulted in lower pain for those undergoing mechanical ventilation (Saadatmand et al, 2015). Combined natural sounds and sights have resulted in lower pain severity compared with both city sounds and sights and with a control during bone marrow aspiration and biopsy (Lechtzin et al, 2010).…”
Section: Sights and Sounds Of Naturementioning
confidence: 99%